Origin and global spread of an endemic chytrid fungus lineage linked to the bullfrog trade - Luisa P. Ribeiro; Julia R. Ernetti; Joice Ruggeri; Thomas S. Jenkinson; Adeline Loyau; Helen Butler; Tina Cheng; Dirk S. Schmeller; Timothy Y. James; Luís Felipe Toledo (Biological Conservation, 2026)

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Designing development programmes for climate change and uncertainty in Pacific Melanesia – the role for knowledge brokers - James R. A. Butler; Seona Meharg; Nicky Grigg; Emily J. Barbour; Hannah Barrowman; Danie Nilsson; Samantha Stone-Jovicich (Climate and Development, 2025)

Environmental visual complexity increases the foraging success of mesopredators by promoting explorative behaviours - Samuel R. Matchette; Samuel J. Butler; Charles E. Redfern Llanos; James E. Herbert-Read (Animal Behaviour, 2025)

X-ray translucent reaction cell for simulation of carbon mineral storage reservoir environments - Ian D. Watt; Ian B. Butler; James Gilgannon; Lucas Martins; Florian Fusseis; R. Stuart Haszeldine; Ian Molnar; Stuart M.V. Gilfillan (International Journal of Greenhouse Gas Control, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

What makes a change agent in environmental conflict transformation? Evidence from rural France - Simon Calla; Lou Lécuyer; James R. A. Butler; Juliette C. Young (Biodiversity and Conservation, 2024)
Transformation of agriculture towards increased sustainability is needed to meet the challenge of declining biodiversity. Nevertheless, stakeholders’ differing perceptions of what sustainability should be, and the multiplicity of possible ways to achieve it can lead to conflictual situations, highlighting the importance of conflict transformation as part of the broader sustainability transformation. If conflict transformation needs to be addressed to prevent the status quo persisting, such processes also reveal the state of social relations and allow us to analyze how collective actions could lead to broader transformations. Using three case studies involving conflicts around pesticide use in the region Bourgogne Franche-Comté (France), we investigate the hypothesis that transformation processes require the engagement of change agents who are motivated and able to overcome barriers to change. Results from 55 in-depth interviews with stakeholders highlight that transformational change depends less on the capacities of a single individual, and more on the mobilization of a plurality of heterogeneous actors (especially farmers, local authorities, and the general public). These actors need to carry out a range of activities that occur with and for others and have an influence on others. According to interviewees, the actors need to engage others, encourage new initiatives, create spaces for knowledge exchanges, and go beyond boundaries. The effectiveness of change agents also depends on the existence of participatory and proactive processes to bring individuals together to create or capitalize on windows of opportunity.

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Urinary concentrations of metals before and after volcanic eruption: a natural experiment surrounding the eruption of Volcán de Fuego, 2018 - Natalie R. Neumann; Jaime Butler-Dawson; Lyndsay Krisher; Diana Jaramillo; Daniel Pilloni; Greg Waite; Yaqiang Li; Stephen B. Wittels; Kathrin Schilling; Lee S. Newman; Katherine A. James (Environmental Geochemistry and Health, 2023)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Fractal domain refinement of models simulating hydrological time series - Abrar Habib; Adrian P. Butler; John P. Bloomfield; James P. R. Sorensen (Hydrological Sciences Journal, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Reconstruction of Atlantic herring ( Clupea harengus ) recruitment in the North Sea for the past 455 years based on the δ 13 C from annual shell increments of the ocean quahog ( Arctica islandica ) - Juan Estrella‐Martínez; Bernd R. Schöne; Ruth H. Thurstan; Elisa Capuzzo; James D. Scourse; Paul G. Butler (Fish and Fisheries, 2019)
Understanding the recruitment variability of the Atlantic herring North Sea stock remains a key objective of stock assessment and management. Although many efforts have been undertaken linking climatic and stock dynamic factors to herring recruitment, no major attempt has been made to estimate recruitment levels before the 20th century. Here, we present a novel annually resolved, absolutely dated herring recruitment reconstruction, derived from stable carbon isotope geochemistry (δ 13 C), from ocean quahog shells from the Fladen Ground (northern North Sea). Our age model is based on a growth increment chronology obtained from fourteen shells. Ten of these were micromilled at annual resolution for δ 13 C analysis. Our results indicate that the anthropogenically driven relative depletion of 13 C, the oceanic Suess effect ( oSE ), became evident in the northern North Sea in the 1850s. We calculated a regression line between the oSE ‐detrended δ 13 C results (δ 13 CṠ) and diatom abundance in the North Sea, the regression being mediated by the effect of phytoplankton on the δ 13 C of the ambient dissolved inorganic carbon. We used this regression to build an equation mediated by a nutritional link to reconstruct herring recruitment using δ 13 CṠ. The reconstruction suggests that there were five extended episodes of low‐recruitment levels before the 20th century. These results are supported by measured recruitment estimates and historical fish catch and export documentation. This work demonstrates that molluscan sclerochronological records can contribute to the investigation of ecological baselines and ecosystem functioning impacted by anthropogenic activity with implications for conservation and stock management.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

Less government intervention in biodiversity management: risks and opportunities - Juliette C. Young; James R. A. Butler; Andrew Jordan; Allan D. Watt (Biodiversity and Conservation, 2012)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Dinosaur remains from the La Quinta Formation (Lower or Middle Jurassic) of the Venezuelan Andes - Paul M. Barrett; Richard J. Butler; Scott C. Moore-Fay; Fernando E. Novas; John M. Moody; James M. Clark; Marcelo R. Sänchez-Villagra (PalZ, 2008)